Autophagy and Mitochondrial Homeostasis During Infection: A Double-Edged Sword - Wang, Sutian; Zhang, Kunli; Yao, Yuchang; Li, Jianhao (Frontiers in Cell and Developmental Biology, 2021)
Autophagy, an essential biological process that affects immunity, is a powerful tool that host cells can use to defend against infections caused by pathogenic microorganisms. Autophagy can not only initiate innate immune responses but also degrade the cellular components that provide the conditions for removing the invaders. However, hyperactivated or inhibited autophagy leads to mitochondrial dysfunction, which is harmful to the host itself and is involved in many types of diseases. Mitochondria perform the functions of biological oxidation and energy exchange. In addition, mitochondrial functions are closely related to cell death, oxygen radical formation, and disease. Accumulation of mitochondrial metabolites affects survival of intracellular pathogens. In this mini-review, we focus on the crosstalk between autophagy and mitochondrial homeostasis during infection.